2012
DOI: 10.1136/bmj.e8268
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the harem conspiracy and death of Ramesses III: anthropological, forensic, radiological, and genetic study

Abstract: This study suggests that Ramesses III was murdered during the harem conspiracy by the cutting of his throat. Unknown man E is a possible candidate as Ramesses III's son Pentawere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…For more detailed information on the sample selection criteria and the methods used see appendix. The study used the maximum available data for the kings of Egypt in physical existence from various sources (Maspero, ; Carter and Maspero, ; Smith, ; Derry, ; Partridge, ; Ikram and Dodson, ; Bickerstaffe, ; Hawass et al, ). From the Old and Middle Kingdom only fragments of royal mummy with dubious identification are known and thus cannot give reliable height information.…”
Section: Methodsmentioning
confidence: 99%
“…For more detailed information on the sample selection criteria and the methods used see appendix. The study used the maximum available data for the kings of Egypt in physical existence from various sources (Maspero, ; Carter and Maspero, ; Smith, ; Derry, ; Partridge, ; Ikram and Dodson, ; Bickerstaffe, ; Hawass et al, ). From the Old and Middle Kingdom only fragments of royal mummy with dubious identification are known and thus cannot give reliable height information.…”
Section: Methodsmentioning
confidence: 99%
“…One can take the published autosomal STR Profile of Ramses III, a ruler from the later 20th Dynasty, ∼200 years later than Tutankhamun and compare it with some of the tested individuals from the 18th Dynasty (Hawass et al, ). Ramses III also shares two partial matches with KV 21A and one full and one partial match with Amenhotep III.…”
Section: Discussionmentioning
confidence: 99%
“…To this regard, complete mummies are much more informative than mummy parts or only bones [1]. Fine examples for the potential of such studies have exemplarily been recently shown by Hawass et al [2], [3] in the case of the mummy of Pharaoh Tutanchamun and other royal mummies from ancient Egypt. Accordingly, any such study seems to be helpful for our understanding of the past.…”
Section: Introductionmentioning
confidence: 99%